2011
DOI: 10.1155/2011/827692
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Candida Species on Clinical Outcomes in Patients with Suspected Ventilator‐Associated Pneumonia

Abstract: Patients with suspected VAP, in whom no bacterial pathogen was identified and in whom Candida species were isolated from RT cultures, exhibited a greater burden of illness compared with similar patients without Candida. Whether Candida species colonization of RT secretions is a marker of disease severity or actually contributes to poorer clinical outcomes remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 37 publications
1
34
0
2
Order By: Relevance
“…is not definitely an innocent bystander in the respiratory tract of ICU ventilated patients [3][4][5][6][7][8][9][10][11][12][13] (Table 1). Beta-glucan (BG), a component of yeast cell wall, may act as a lung proinflammatory agent causing alveolar macrophage and neutrophil dysfunction.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…is not definitely an innocent bystander in the respiratory tract of ICU ventilated patients [3][4][5][6][7][8][9][10][11][12][13] (Table 1). Beta-glucan (BG), a component of yeast cell wall, may act as a lung proinflammatory agent causing alveolar macrophage and neutrophil dysfunction.…”
mentioning
confidence: 99%
“…Live Candida albicans instillation in rats has been observed to increase the susceptibility to develop experimental Pseudomonas aeruginosa (PA), Escherichia coli (Ec), and Staphylococcus aureus (Sa) pneumonia, fostering the production of lung inflammatory cytokines (tumor necrosis factor alpha [TNF-alpha], interleukin-6 [IL-6], and interferon-gamma [INF-c]) and inhibiting alveolar macrophage phagocytosis [3,5]. From a clinical viewpoint, Candida airway colonization has been shown to be associated with prolonged duration of mechanical ventilation, ICU/hospital length of stay, and increased mortality [8][9][10][11]. One of the first reports of this possible relationship dates back to almost 10 years ago, when Azoulay et al [6] identified Candida bronchial isolation as an independent risk factor for the development of PA ventilator-associated pneumonia (VAP) (9 vs 4.8 % in non-colonized patients, p = 0.048).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the EORTC/MSG definitions of IFD, fever is not a host factor, and due to the lack of specificity is only considered a clinical sign [41]. However, persistent fever, in particular when antibiotics are used ineffectively, can often suggest a fungal infection [41,42]. In such case, if clinical signs and host factors are present, without the conformation in mycological tests, the criteria of possible IFD are fulfilled.…”
Section: Diagnostic Methods To Prove Fungal Infectionmentioning
confidence: 99%